1978
DOI: 10.1111/j.1399-3054.1978.tb01605.x
|View full text |Cite
|
Sign up to set email alerts
|

Organogenesis and Plantlet Formation from Organ‐ and Seedling‐Derived Calli of Rice (Oryza sativa)

Abstract: Callus was induced in different somatic organs of Oryza sativa L. Specific minimum 2,4‐dichlorophenoxyacetic acid (2,4‐D) concentrations in the medium were necessary for the induction of callus from different organs while high levels of 2,4‐D (6–10 mg/l) induced callus formation in each organ tested. The optimum 2,4‐D concentration for callus induction and growth for root‐derived calli was 2 mg/l and for leaf‐derived 6 mg/l. Root and shoot organogenesis were induced in both root‐ and leaf‐derived calli by sub‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Development of simple method to regenerate highly fertile plants in a relatively short period of time is desirable to achieve genetic modification in crop plants like rice. It was demonstrated that 1-5 mm segments of leaf base of 3-4 days old rice seedlings were most suitable for the induction of callus as compared to any other seedling derived organ (Henke et al, 1978). In the present study using 8 different concentrations (0.5-4.5 mg L -1 ) of 2,4-D, only 2.5 mg L -1 showed maximum callus induction and mean fresh weight.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Development of simple method to regenerate highly fertile plants in a relatively short period of time is desirable to achieve genetic modification in crop plants like rice. It was demonstrated that 1-5 mm segments of leaf base of 3-4 days old rice seedlings were most suitable for the induction of callus as compared to any other seedling derived organ (Henke et al, 1978). In the present study using 8 different concentrations (0.5-4.5 mg L -1 ) of 2,4-D, only 2.5 mg L -1 showed maximum callus induction and mean fresh weight.…”
Section: Discussionmentioning
confidence: 77%
“…Despite a large number of reports on rice tissue culture, there is significant genotype-dependence, and in vitro regeneration of indica rice is still a challenging task (Kumria et al, 2000). There are several successful reports on regeneration from explants such as leaf blade (Yan and Zhao, 1982), root tips (Sticklen, 1991), leaf sheath/leaf sections (Wernicke and Milkovits, 1984), immature panicles (Shu and Wei, 1980), mature seed embryos (Ramesh and Gupta, 2006), immature embryo (Koetje et al, 1989), coleoptile (Oinam and Kothari, 1995), anthers (Genovesi and Magill, 1982), stem nodes (Furuhashi and Yatazuva, 1964), seedling derived mesocotyl segments (Mascarenhas et al, 1975), leaf segments (Henke et al, 1978) and leaf bases (Ramesh et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Ngezahayo1 et al (2007) studied the nature of somaclonal variation at the nucleotide sequence level in the cultivar rice Nipponbare using RAPD and ISSR markers and by pairwise sequence analysis. Earlier reports on somaclonal variation in rice include those of Nishi et al (1968) and Henke et al (1978), all from rice callus. Variations were observed in number of tillers per plant, number of fertile tillers per plant, length of panicle, frequency of fertile seeds, plant stature and length of flag leaf.…”
Section: Genetic Basis Of Somaclonal Variationmentioning
confidence: 99%
“…Callus grown on media A, B, and F showed the same response, but significantly more callus growth than on media C, D, and E . (Lo et al, 1980), and rice (Henke et al ., 1978), but not in smooth bromegrass and crested wheatgrass (Lo et al ., 1980) . In this study, the less amount of kinetin (0 .2 mg 1-') promoted shoot formation in smooth bromegrass callus culture in some instances .…”
Section: Callus Inductionmentioning
confidence: 99%